2010
DOI: 10.1111/j.1365-2842.2009.02055.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of communication and master impressions for the fabrication of cobalt chromium removable partial dentures in general dental practice in England, Ireland and Wales in 2009

Abstract: The aim of this study was to investigate the quality of communication and master impressions for the fabrication of cobalt chromium removable partial dentures (RPDs) in general dental practice in England, Ireland and Wales in 2009. Two hundred and ten questionnaires were distributed to 21 laboratories throughout England, Ireland and Wales. Information was collected regarding the quality of written communication and selection of master impression techniques for cobalt chromium partial dentures in general dental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 25 publications
4
41
3
1
Order By: Relevance
“…Scrutinising dentists’ prescriptions indicated that delegating the design of the cobalt chromium FESRPD entirely to the dental technician is a common practice among a considerable proportion of dentists in this survey (32%). This is in line with previous surveys that reported poor quality of communication with respect to cobalt chromium RPDs design (22–26) and warrant further investigations to underline the reasons behind the continuation of such kind of inadequate practice. Moreover, the impact of such clinical behaviour on the highly reported failure rate of FESRPDs needs to be further investigated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Scrutinising dentists’ prescriptions indicated that delegating the design of the cobalt chromium FESRPD entirely to the dental technician is a common practice among a considerable proportion of dentists in this survey (32%). This is in line with previous surveys that reported poor quality of communication with respect to cobalt chromium RPDs design (22–26) and warrant further investigations to underline the reasons behind the continuation of such kind of inadequate practice. Moreover, the impact of such clinical behaviour on the highly reported failure rate of FESRPDs needs to be further investigated.…”
Section: Discussionsupporting
confidence: 91%
“…Kilfeather et al. (26) found only 37% of written prescriptions were accompanied by a diagram. In this study, only 26 written prescriptions (29%) were accompanied by a diagram.…”
Section: Discussionmentioning
confidence: 99%
“…While in recent years there have been improvements in compliance with infection control procedures, some aspects remain problematic. 13 Dental laboratory personnel are in a position to minimise contamination of appliances during stages of production and as such should give consideration to potential areas of improvement. Jagger et al 14 indicated that there was a low level of interest by laboratory staff towards infection control among their sample of 800 dental laboratories.…”
Section: N B R I E F Practicementioning
confidence: 99%
“…Regardless of the increasing demand for implant-based restorations, RPDs offer the advantages of avoiding the surgical risks, complexity and costs associated with implant treatments (4,5). Nevertheless, for some many years, it has been recognized that problems exist among the dental profession when prescribing, designing, and fabricating removable partial dentures (6)(7)(8)(9), despite the introduction of the European Union's "Medical Devices Directive" in 1993. This Directive placed specific requirements on dental practitioners "to provide adequate written instructions when a prosthesis is being manufactured, and that dental laboratories manufacture the prosthesis to this specification".…”
Section: Introductionmentioning
confidence: 99%